Effect of Urea and Humic acid fertilization on some chemical/physical Properties and yield of cow pea Vigna unguiculata (L.) walp - AL-Kaaby , Mohammed (University of Thi-Qar Journal of Science, 2012)
This study was conducted in AL-Qaraf region, Thi-Qar province, to study the effect of earth fertilization by Urea and Humic acid on some chemical/physical properties and yield of cow pea. A local cultivar of cowpea was planted during autumn seasons of 2009 a factorial experimental design within R.C.B.D with three replicates was used with two factors. The first factor was the Urea (46%) with three levels (0, 10 and 15kg N/ dunam). The second factor was the humic acid with three levels (0, 300 and 600 g / dunam). the result showed that :( 15kg N/ dunam) and (600 g humic acid / dunam) treatment gave asignificant superiority on the all studies characterstic (the ratio of protien , carbohydrate content in cowpea seeds tissues , leaves content of (NP-K) and (The mean number of nodules , branches/plant , leaf area and plant height respectively) also ( thepods weight /plant and gave higher total yield (1.77 ton/dunam) (1.52 ton/dunam) respectively) as compared with other treatments . Interaction treatments result showed that; (15kg N/ dunam) + (600 g humic acid / dunam) treatment gave asignificant superiority at (the ratio of protein, the mean number of nodules), and for (leaf area as well as branches/plant and plant height) respectively as compared with other treatments. (10kg N/ dunam) + (600 g humic acid / dunam) treatment gave asignificant superiority on the other studies characterstic with( carbohydrate content in cowpea seeds tissues .